Analisis Psikologi terhadap Adab-adab Guru dalam Kitab Adab al-Alim wa al-Muta’allim - Munawwir, Muhtar Tajuddin; Abdul Muhid (Program Pascasarjana Universitas Ibrahimy, 2020)
This study aims to analyze the teachers' manners contained in the book of Adab al-Alim wa al-Muta’allim by K.H.M. Hasyim Asya'ari from a psychological perspective. This study was a qualitative study with a literature review approach. These manners had been classified into several categories and then were analyzed with a psychological perspective. The results showed that, first, the teachers' manners could be classified into 6 categories. They are manners related to inner behavior, prayer and practical deed, exemplary, scientific competence, good relationship, and teaching techniques. Second, After had been analyzed from a psychological perspective, the results showed that manners being related to inner behavior, prayer, and practical deed were relevant with al-Quran dan al-Hadits; manners being related to exemplary and scientific competence were associated with Bandura's social cognitive theory; manners being related to a good relationship and teaching techniques were linked with the theory of cognitivism and humanism.